Piloting an ICT-based App for providing weather forecasts, agroadvisory and market information to smallholder farmers in Ethiopia - Fikreyesus, Daniel; Tesfaye, Lidya; Nebsu, Bayu; Ambaw, Gebermedihin; Recha, John W.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Agriculture is the core sector of the Ethiopian economy (Bekabil 2014). However, smallholder farmers that dominate the sector practice rain-fed mixed farming by using unimproved practices leading to low agricultural productivity (Welteji 2018). Ethiopian agriculture is also vulnerable to climate-related risks such as more frequent droughts and flooding, rainfall variability, and heatwaves (high temperatures) (Amsalu 2009). The impacts of hazards related to current weather variability and climate extremes have already been felt in the country. It is projected that by the year 2050, the negative impacts of climate change, under an extreme scenario of higher temperatures and increased intensity and frequency of extreme events, could cost Ethiopia 8-10% of its Gross Domestic Product (GDP) (Robinson et. al. 2013).